Računalniška aplikacija za oceno socialnoekonomskih in okoljskih vplivov povečane rabe lesne biomase - primerjava rezultatov med izbranima regijama v Sloveniji in na Hrvaškem - Krajnc, Nike (Zbornik gozdarstva in lesarstva, 2005)
Wood biomass is an important renewable source of energy, which can have numerous positive socio-economical and environmental effects. In the present article we would like to present a new model for the estimation of 15 socioeconomic and environmental aspects of the increased use of wood biomass. The presented model enables a selected estimation of different aspects in different chains of biomass production, preparation and use, as well as an estimation of the following socio-economic and environmental aspects: net labour income, net profit, regional public finance receipts, net direct jobs, net indirect jobs, net induced jobs, total net jobs, contribution to forest management, impact on wood waste utilization, impact on other woody biomass utilization, avoided costs of land fuel, saving CO2 emissions, possible impacton regional unemployment, avoided costs of unemployment, additional jobsfor farmers, additional activities on farms (from indirect and induced jobs) and self-sufficiency in electricity production. The most important is the estimation of new jobs, which is the reason why they were divided into direct, indirect and induced now jobs. The model was tested in two selected region in Slovenia and in Croatia.
Keywords: lesna biomasa; obnovljivi energetski viri; raba energije; računalniški modeli